2002
DOI: 10.1002/ppul.10164
|View full text |Cite
|
Sign up to set email alerts
|

Airway obstruction in children with congenital heart disease: Assessment by flexible bronchoscopy

Abstract: We assessed the spectrum of airway disorders in children with congenital cardiac anomalies, and reviewed our experience in using flexible bronchoscopy for assessment of airway problems in this patient group. The clinical records, flexible bronchoscopic findings, and cardiac imaging results of pediatric cardiac patients who presented with either clinical or radiological signs of airway obstruction between 1992-1999 were reviewed. Flexible bronchoscopic assessment was performed with the patients under sedation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
62
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 24 publications
5
62
0
2
Order By: Relevance
“…The spectrum of airway diseases observed is similar to that described in previous studies (1,11,12). Herein, the most common bronchoscopy diagnoses of airway abnormalities consisted of external compression of airways, tracheobronchomalacia, and airway narrowing, which are associated with cardiovascular abnormalities such as ASD, VSD, and PDA.…”
Section: Discussionsupporting
confidence: 78%
“…The spectrum of airway diseases observed is similar to that described in previous studies (1,11,12). Herein, the most common bronchoscopy diagnoses of airway abnormalities consisted of external compression of airways, tracheobronchomalacia, and airway narrowing, which are associated with cardiovascular abnormalities such as ASD, VSD, and PDA.…”
Section: Discussionsupporting
confidence: 78%
“…In children with persistent recurrent respiratory distress, unexplained atelectasis, or extubation failure, the possibility of airway compression should be strongly suspected [13][14][15][16]. In this study, the findings imply that the location of tracheobronchial compression caused by tortuous and dilated large and medium-sized thoracic arteries can be very different.…”
Section: Discussionmentioning
confidence: 68%
“…6 Congenital airway anomaly is believed to be significantly associated with CHD, 4,31-34 and early identification is essential for appropriate management. 32,35 Here, we demonstrated that congenital airway anomaly was an independent risk factor for tracheostomy in infants with CHD. Tracheostomy placement may improve outcomes; therefore, timely diagnosis and optimal management of congenital airway anomaly are essential.…”
Section: Discussionmentioning
confidence: 96%